Pengembangan Services Untuk Menghubungkan Aplikasi Human Resource Information System (HRIS) Dengan Modul Hr SAP - Meyliana, Meyliana (Bina Nusantara University, 2010)
Rapid business changes also trigger changes in interconnected applications. Changing multiple interrelated applications, have a level of difficulty and complexity of its own, especially if the platform and framework of these applications are not the same. One of the concepts that can help bridge the time gap problem between business change with changes in applications and platforms and frameworks to bridge the gap between applications is the implementation of